Frontispiece: A conjugated polymer‐liposome complex: A contiguous water‐stable, electronic, and optical interface (View 1/2021). Issue 1 (6th February 2021) - Jephcott, Lilli; Eslami, Minoo; Travaglini, Lorenzo; Lauto, Antonio; Mawad, Damia
Abstract : In article numer 20200081, Damia Mawad and co‐workers highlight the importance of coupling conjugated polymers and conjugated polyelectrolytes with the lipid bilayer to engineer interfaces with unique characteristics, facilitated by accessing the properties of each constituent material. Conjugated polymers provide optical and electronic properties, whereas the lipid bilayer mimics the biological cell, enabling fusion with the cell membrane. The cover summarises how utilising these conjugated polymer‐liposome complexes to establish an intimate electronic connection with the cell membrane holds great potential, providing the possibility to access and control, via electronic conductivity, cell membrane structures in electroconductive tissue such as the heart and brain.